2010
DOI: 10.1111/j.1552-6569.2010.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

What ASPECTS Value Best Predicts the 100-mL Threshold on Diffusion Weighted Imaging? Study of 150 Patients with Middle Cerebral Artery Stroke

Abstract: ASPECTS may serve as a surrogate marker of infarct extent on DWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
(26 reference statements)
2
19
1
1
Order By: Relevance
“…This explains the wide range of true lesion volumes for a given DWI-ASPECTS point found here, in line with other studies. 2,7 Our finding that DWI-ASPECTS <4 invariably predicted Vol DWI ≥93 mL is entirely consistent with 1 previous report 7 and highly relevant to the Diffusion and perfusion imaging Evaluation For Understanding Stroke Evolution (DEFUSE)-2 malignant profile 100 mL cut point. 4 However, patients with DWI-ASPECTS ≥7 all had Vol DWI <70 mL, which corresponds to the cut point incorporated in the target mismatch definition.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…This explains the wide range of true lesion volumes for a given DWI-ASPECTS point found here, in line with other studies. 2,7 Our finding that DWI-ASPECTS <4 invariably predicted Vol DWI ≥93 mL is entirely consistent with 1 previous report 7 and highly relevant to the Diffusion and perfusion imaging Evaluation For Understanding Stroke Evolution (DEFUSE)-2 malignant profile 100 mL cut point. 4 However, patients with DWI-ASPECTS ≥7 all had Vol DWI <70 mL, which corresponds to the cut point incorporated in the target mismatch definition.…”
supporting
confidence: 79%
“…In the first 6 hours, we assessed the relationships between DWI-ASPECTS and Vol DWI in patients with middle cerebral artery stroke. We particularly focused on one hand, on DWI-ASPECTS cut points previously reported to be associated with Vol DWI >100 mL (<4 7 ), hemorrhagic transformation (<6 1 and <8 2 ), or outcome (<5 1 , <6 1,8 , <7 9 , and <8 10 ) and, on the other hand, on the 70 and 100 mL Vol DWI cut-offs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 The DWI-ASPECTS can also provide similar risk assessment far more rapidly than measurement of the infarct volume on DWI, an independent predictable marker of the clinical outcome, in patients with anterior circulation stroke. 9,[15][16][17] However, few studies have investigated the association between pretreatment DWI-ASPECTS and functional outcome after stent-retriever embolectomy in patients with acute anterior circulation stroke. 9,14,18 Although several studies showed that a DWI-ASPECTS of 7 was the optimal cutoff value for predicting clinical outcomes in patients undergoing intra-arterial or IV pharmacologic thrombolysis, [19][20][21] results of recent studies have suggested that some patients with a DWI-ASPECTS of Ͻ7 may still benefit from complete recanalization.…”
mentioning
confidence: 99%
“…This has been shown about DWI in large populations with stroke, with excellent correlation between this semiquantitative and the volumetric approach, 10,11,20 offering the possibility of using extreme DWI-ASPECTS scores as surrogates for important volume cut points. 10,21 About PWI and PWI/ DWI mismatch, the correspondence between ASPECTS and volumetric measurements has received little attention so far.…”
Section: October 2016mentioning
confidence: 99%